English-Speaking Immigrants in Israel During the Pandemic: Challenges and Pathways to Resilience: מהגרים דוברי אנגלית בישראל בתקופת המגיפה: אתגרים עיקריים ומסלולי חוסן. (February 2023) - Dryjanska, Laura; Zlotnick, Cheryl; Suckerman, Suzanne
This qualitative study explores the resilience of a community of 108 English-speaking immigrants in Israel facing the stress of the COVID-19 pandemic. It features the social constructivist approach to resilience as a negotiation of adversities using coping strategies understood within the framework of control, coherence, and connectedness. We discuss data in an articulated perspective of themes comprised of language barriers, transnationality, and the us/them divide, which constitute a common thread in the negotiation of resilience. The pathways to resilience, geared to help individuals in the meaning-making process, build distress tolerance, increase social support, embrace a view of a deep human interconnectedness, and take goal-directed value-driven actions, constituting a basis for interventions. Counseling practice should offer English-speaking immigrants to Israel specific resources that encourage acceptance-based coping, culturally relevant practices of mindfulness, as well as tools that promote social interactions and build resilience by cultivating positive emotions and social connection.